2019
DOI: 10.1136/tobaccocontrol-2018-054900
|View full text |Cite
|
Sign up to set email alerts
|

Measuring e-cigarette addiction among adolescents

Abstract: Background and objectivesWith high rates of use and uncertain consequences, valid electronic cigarette (e-cigarette) use frequency and addiction measures for adolescents are needed. This cross-sectional study examined correlations for multiple measures of adolescent e-cigarette use with nicotine exposure quantified with salivary cotinine levels.MethodsAdolescents (N=173, age 13–18) who reported past-month e-cigarette use were recruited from the San Francisco Bay Area. Participants self-reported: (1) days of e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…Previous studies have provided less comprehensive characterizations of e-cigarette dependence, without comparisons with combustible cigarette dependence. 6 8 To our knowledge, this is also the first prospective longitudinal investigation of the association of e-cigarette dependence symptoms with subsequent vaping patterns. Our results suggest that e-cigarette dependence symptoms may be associated with future vaping patterns.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have provided less comprehensive characterizations of e-cigarette dependence, without comparisons with combustible cigarette dependence. 6 8 To our knowledge, this is also the first prospective longitudinal investigation of the association of e-cigarette dependence symptoms with subsequent vaping patterns. Our results suggest that e-cigarette dependence symptoms may be associated with future vaping patterns.…”
Section: Discussionmentioning
confidence: 93%
“…Ecigarette use frequency in a typical month was self-reported ranging from 0 to 30 days. E-cigarette dependence was measured using the 10-item Penn State Electronic Cigarette Dependence Index (scored as 0e3 ¼ not dependent; 4e8 low dependence; 9e12 medium dependence; 13þ ¼ high dependence) [23], which was strongly correlated with cotinine levels in this sample [24]. Salivary cotinine was measured at baseline, 6, and 12 months.…”
Section: Methodsmentioning
confidence: 97%
“…Importantly, the uses of e-cigs induce a comparable urge to smoke and increase the desire for conventional combustible smoking [ 9 ]. Studies have demonstrated an addictive-like behavior with e-cigs use in clinics [ 10 ]. Nicotine represents the addictive component in e-cigs, which is found in most e-liquids in the market [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%